1993
DOI: 10.1111/j.1365-2958.1993.tb01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Homology between a genetic locus (mdoA) involved in the osmoregulated biosynthesis of periplasmic glucans in Escherichia coli and a genetic locus (hrpM) controlling pathogenicity of Pseudomonas syringae

Abstract: Membrane-derived oligosaccharides (MDO) of Escherichia coli are representative members of a family of glucans found in the periplasmic space of Gram-negative bacteria. The two genes forming the mdoGH operon are necessary for the synthesis of MDO. The nucleotide sequence (4759 bp) and the transcriptional start of this operon were determined. Both gene products were further characterized by gene fusion analysis. MdoG is a 56 kDa periplasmic protein whose function remains to be determined. MdoH, whose presence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 65 publications
2
74
0
3
Order By: Relevance
“…opg (or mdo) mutants have been associated with a lack of virulence in phythopathogenic bacteria such as Pseudomonas syringae and Er. chrysanthemi (Loubens et al, 1993;Mukhopadhyay et al, 1988;Page et al, 2001). Unlike the tol-pal mutants, the opgGH mutants show a complete loss of virulence, even on potato tubers, but present some phenotypes similar to those observed for the tol-pal mutants, namely reduced motility and pectate lyase production (Page et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…opg (or mdo) mutants have been associated with a lack of virulence in phythopathogenic bacteria such as Pseudomonas syringae and Er. chrysanthemi (Loubens et al, 1993;Mukhopadhyay et al, 1988;Page et al, 2001). Unlike the tol-pal mutants, the opgGH mutants show a complete loss of virulence, even on potato tubers, but present some phenotypes similar to those observed for the tol-pal mutants, namely reduced motility and pectate lyase production (Page et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…For example, the hrpM mutant of Pseudomonas syringae pv. syringae does not synthesize OPGs and loses its ability to cause brown spot disorder on common bean (Phaseolus vulgaris) (Loubens et al, 1993). P. aeruginosa contains gene homologues for linear and cyclic OPGs (Stover et al, 2000) and it has been shown that transcripts for (cyclic) OPG synthesis are stimulated in P. aeruginosa cells grown in biofilms (Mah et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In Enterobacteria and related bacteria, both products of the opgGH operon are required for synthesis of the glucose backbone of OPGs. opgG or opgH mutant strains are completely devoid of OPGs and exhibit a reduced or non-virulent phenotype, indicating that these glucans belong to the common virulence factors of many zoopathogens and phytopathogens (Loubens et al, 1993;Mahajan-Miklos et al, 1999;Page et al, 2001).…”
Section: Introductionmentioning
confidence: 99%